C.05 Canadian neurosurgery operative landscape. (17th June 2016) - Tso, MK; Bigder, M; Dakson, A; Elliott, C; Guha, D; Iorio-Morin, C; Kameda-Smith, M; Lavergne, P; Makarenko, S; Taccone, M; Wang, B; Winkler-Schwartz, A; et al.
Abstract : Background: The Canadian Neurosurgery Research Collaborative (CNRC) is a trainee-led multi-centre collaboration made up of representatives from 12 of 14 neurosurgical centres with residency programs. To demonstrate the potential of this collaborative network, we gathered administrative operative data from each centre in order to provide a snapshot of the operative landscape in Canadian neurosurgery.Methods: Residents from each training program provided adult neurosurgical operative data for the 2014 calendar year, including the number of surgeries in the subcategories cranial, spinal, and peripheral nerve. Because some residency programs have surgeries distributed among more than one hospital, we calculated mean case load per residency program and per hospital.Results: Interim results from 6 neurosurgery residency programs are presented (with data from other programs forthcoming). Overall, there were on average 2, 352 operative cases per residency program ( n =6) and 1, 176 operative cases per adult hospital ( n =12). Among 5 programs with more detailed operative data, the mean numbers of cranial, spinal, peripheral nerve, and miscellaneous surgeries per residency program were 757 (47%), 487 (30%), 47 (3%), and 319 (20%) respectively.Conclusions: We show as a proof-of-concept that a trainee-led nation-wide research collaborative can generate meaningful data in a Canadian context.